Miranda Molinar: capstone - Molinar, Miranda, artist (Colorado State University. Libraries, 2014)
The artist's statement: My artwork reflects on my interest in tattoos. Tattoos have influenced my art tremendously as well as created a new passion and life for my work both visually and conceptually. They are explored in my work through various ways such as through media, imagery, technique, style, content, etc. I have worked with various materials; such as latex, paints, markers, found objects, found images, various papers, sculpture, and paper folding to communicate my ideas. Each artwork embodies the idea of tattoo, although it may not always be apparent. Tattoos to me are much more than embellishing the body; they tell a story and bring life to a person's body. Through my work I investigate the cultural and ornamental significance they have to me, as well as show the world they create for me.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.